Izvedba univerzalne ontologije geografskega prostora v podmnožici predikatnega računa prvega reda - Čeh, Marjan (Geodetski vestnik, 2012)
Spatial data sources, like the geodetic reference system, administrative spatial units, addresses and topographic maps, serve as a base for geo-referencing to the most of dependant thematic spatial databases. The marketing strategy of the surveying profession towards the users of spatial data infrastructure should be in the design of an integrative semantic reference system to be used within the Semantic Web, or so-called Web 3.0. Themain motivation for our research was the representation of possibilities toautomate tool development for efficient and more sensible approaches to query information within web-published spatial data. In contemporary research there are several solutions offered as upgrades of basic GIS systems with the knowledge presented in the form of ontologies. Therefore, we are faced with the new generation of GIS technology, which has been named "inteligent GIS". In this article, we present method of modelling the semantic reference system as an application of the ontology of geographic space in the subset of first order predicate calculus. Such a semantic network of geographic space represents the foundation for semantic data analyses and data integration in distributed information systems. Our application is based on the methods of machine learning and use of the Prolog programming language.
Keywords: geografski prostor; GIS; logic; logika; ontologija; ontology; predicate calculus; predikatni račun; prostorski podatki; Semantic Web; semantični splet